Zambian Mole-Rats: 33 Years on the Scene and What We Still Do Not Know and How We Could Learn It - Burda, Hynek (Frontiers in Ecology and Evolution, 2022)
Here, I survey my more than three decades lasting research on Zambian mole-rats (genus Fukomys, Bathyergidae), point out some unanswered questions and untested hypotheses and suggest approaches to address them. The research proposals range from sensory ecology topics, which was my main research field, covering different (even not yet identified) senses, orientation in time and space, communication, studies on ageing, population dynamics and survival strategies of mole-rats during yearly floodings in the Kafue Flats, cryptozoological investigation into the existence of strange mole-rat species in some Zambian localities reported to us by natives, study of mole-rats in assumed contact (hybrid?) zones of special interest, (cyto)genetic studies of hybrids of selected species, non-invasive study of population and family structure and dynamics with help of endoscopes. In each case, I provide rationale, reasoning, hypothesis, and suggest methodical approach.